THE SOCIAL SECURITY SYSTEM OF INDIVIDUALS AS A KEY DETERMINANT IN IMPLEMENTING THE ECONOMIC POLICIES OF BUSINESS ENTITIES - Zakharii Varnalii; Oksana Mykytiuk; Tetiana Onysenko; Ihor Pampukha (Academy Review, 2025)
In response to the complex socio-economic changes caused by the ongoing military conflict in Ukraine, this article explores the critical role of employee social security systems within enterprises as a foundation for sustainable business development and effective economic policy implementation. Social security has become an indispensable factor for companies operating in uncertain environments, where the well-being and stability of employees directly impact productivity, engagement, and long-term resilience. Recognizing these dynamics, the authors aim to provide a comprehensive understanding of social security as a primary driver in managing corporate economic policies and enhancing organizational stability, particularly in challenging wartime conditions. The social security system for individuals employed by entrepreneurial entities encompasses a broad range of policies, programs, and practices designed to protect employees’ welfare and mitigate risks arising from economic volatility, external threats, and internal vulnerabilities. In the face of military aggression, these policies must go beyond conventional frameworks, aligning with corporate social responsibility (CSR) strategies that address not only economic but also social priorities within the broader corporate management paradigm. This article argues that modern management theories and practices in Ukraine require stronger methodological and practical support to develop social security frameworks that prioritize the well-being of the workforce as a strategic asset. A key aspect of this work is the critical examination of CSR and its role in constructing resilient social security systems. Through a review of recent literature and methodologies, including studies on internal CSR mechanisms, the authors highlight how modern enterprises can create favorable conditions for highly qualified personnel, which are crucial for navigating complex production challenges. However, a gap remains in Ukrainian business practices regarding the implementation of CSR models focused on internal social security—a gap that is particularly significant during crises such as wartime and post-war recovery. This article addresses this gap by providing a comprehensive analysis of CSR- based social security and its potential to enhance employee morale, loyalty, and productivity under adverse conditions. The article also explores the importance of fostering corporate citizenship, where companies take on roles akin to «good citizens» by contributing to regional and national stability through social initiatives. Such actions not only enhance a company’s reputation but also create a supportive environment that benefits both employees and the wider community. In this context, the authors propose practical recommendations for developing a CSR framework that integrates social security into the core of economic policy and operations, emphasizing the value of community-oriented and resilient practices.